Detection of Non-tuberculous mycobacteria hsp65 in some ruminant’s subclinical mastitis milk and rheumatoid arthritis patient’s blood - Namaat R. Abdullah; Fawziah A. Abdullah (Basrah Journal of Veterinary Research)
The main aim of this study was to detect non-tuberculous mycobacteria hsp65   in animal’s subclinical mastitis milk and Rheumatoid arthritis patients blood. Modified White Side Test (MWT) was used as a preliminary screening test for subclinical mastitis in 70 cows ,50 ewes and 30 goats milk samples. The results of this test revealed that 58(82.9%), 38(76%) and (46.7%) of cows, ewes and goats milk samples respectively were  positive with significant difference(P<0.05). Statistically significant (P<0.05) varying score of positivity was observed by this test, as a follow; score (+++)  in cows (37.93%) and ewes (28.9%) milk samples only , score (++)  in all cows, ewes and goats milk samples at different percentage(18.96,21.1 and14.3%, respectively) and score (+) in cows (43.11%,), ewes (50%) and goats(85.7%) milk samples. Molecular detection of non-tuberculous mycobacteria (NTM)16SrRNA gene in Milk samples revealed that 3(6%) and 11 (22%) cows and ewes milk samples respectively showed positive results with significant difference(P<0.05). The NTM hsp65 gene (441 bp) was detected in 50(71.4%) and10 (20%) milk samples  of cows and ewes respectively with significant difference(P<0.05).This gene also detected in 3) 33.3% ( rheumatoid arthritis patients blood samples with  an overall percentage of  7.5% and negative results for this genewas observed in non rheumatoid arthritis patients blood samples with significant difference(P<0.05). The hsp65 gen sequencing results confirmed high sequence similarity (99%) of the current hsp65 (441 bp ) sequences with Mycobacterium avium retrieved DNAsequences (GenBank acc. NZ_CP009360.4).